Bicultural encounter. (3rd July 2019) - Haenga-Collins, Maria; Solomon, Margot; Woodard, Wiremu; Rodgers, Brian; Tudor, Keith
ABSTRACT: This article discusses large group encounter in the context of biculturalism, a concept that is specific to the relationship and engagement between indigenous and settler cultures, especially, though not exclusively in countries such as Aotearoa New Zealand, Australia, Canada, and the United States of America. It is written by five colleagues who work in the same tertiary educational institution, albeit in different roles. The discussion is framed in the context both of person-centered approaches to encounter and of group analytic approaches to large groups. It is illustrated with reference to a practice of community kōrero (speech, discussion, conversation), and a way of facilitating a group theory and practice paper (class), following which the last two parts of the article offer some critical reflections on the interface between culture, specifically in a bicultural context, and encounter.